Perspectives of Digital and it Development: Modeling for EU Countries - Полозова, Т. В.; Худяков, Д. Л.; Вешкін, Є. П. (ХНУРЕ, 2023)
Digital Technologies radically change traditional business models and principles of work organization. Due to data of World Economic Forum, 85 % customer/citizent engagement in 2020 is done without human interaction. 65 % of today’s children will work on new jobs types, that are currently don’t exist yet. 57 % of jobs are at risk of automation. 80 % of business leaders pointed out, that the digital way of working is a main enabler to company success. Successful companies at the current stage of development of mechanisms of digital transformation. Digital transformation changes the usual business models and affects changes in society.
Keywords: digital development; IT development; digital transformation; EU countries